Decentralization policies in public administration in Slovakia and the Czech Republic, and their impact on building offices' scale efficiency - Peter Fandel; Eleonora Marišová; Tomáš Malatinec; Ivana Lichnerová (Administrative Sciences, 2019)
Decentralization policy schemes (DPSs) in the public sector have been implemented in different ways by Slovakia and the Czech Republic. Both approaches have led to a transfer of competencies from state administration to self-government with the aim of improving the efficiency of the delivery of services. This paper presents a comparative scale efficiency analysis of the units performing services in the building order sector. The analysis is based on two unique regional datasets from two countries, Slovakia and the Czech Republic. The DPS implemented in Slovakia is based on the principle of voluntary cooperation of municipalities. In the case of the Czech building sector, the competencies have been transferred to the newly created municipalities with delegated or extended competencies. This study aims to contribute to the research on efficiency in public administration. We focused on the relationship between two types of DPSs, and units' scale efficiency. We also tried to determine whether a specific unit scale size could be identified as the most efficient. We employed a two-stage metafrontier approach based on procedures for evaluating program and managerial efficiency. The results show that different DPs have not led to statistically significant differences in performance, and it is not possible to identify the most efficient building office scale size.
Keywords: 350; decentralization; local self-governments; building sector; building offices; scale efficiency; data envelopment analysis; metafrontier